An Empirical Study on Restrictive Laws and Regulations Affecting Women’s Economic Participation - Naape, Baneng (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
The global emphasis on women's economic participation has grown significantly due to its vital role in promoting macroeconomic stability and advancing financial inclusion. Involving women in economic activities is essential for achieving Sustainable Development Goals, such as poverty alleviation and closing gender gaps. However, a range of regulatory, cultural, and structural barriers continue to hinder women’s ability to participate in the mainstream economy. This study aims to examine the impact of restrictive laws and regulations on women’s economic participation within the BRICS bloc. Women’s economic participation has been examined through three key dimensions: paid employment, political representation, and entrepreneurship. The findings suggest that the removal of restrictive laws and regulations is associated with increased levels of women's economic participation. It is important to acknowledge that while BRICS countries have made significant strides in dismantling legal barriers affecting women, substantial obstacles remain from both legal and regulatory perspectives that hinder women’s engagement in economic activities. Therefore, the study recommends that BRICS nations prioritize the complete removal of restrictive laws and regulations impacting various aspects of women's lives, including mobility, pay, marriage, and entrepreneurship.. Furthermore, ensuring a gender-equitable distribution of resources should be a central focus in policymaking to ensure that no one is left behind in the development agenda, particularly women and children.